DINAMIKA POPULASI LALAT BUAH PADA TANAMAN HORTIKULTURA - Juniawan Juniawan (AgriPeat, 2020)
Fruit flies are the major pest in vegetable and fruit plants, both in rainy and dry seasons. Plants that are attacked become damaged and rot. This study aims to determine the dynamics of fruit fly populations on the campus of the Indonesian Centre Agricultural Training (ICAT) Ketindan. This study conducted for 3 weeks in January 2020. This research was observational by setting fruit fly traps from 600 ml of mineral water bottles. 18 traps were hung on a tree at a height of 2 meters from the top of the land surface randomly and spread over an area of 4.7 hectares. Each trap was dropped 0.5 ml of methyl eugenol on cotton which was placed at the end of the wire in a dependent position and filled with 100 ml of clean water below it. Observations were made by collecting trapped fruit flies every morning. The yields are calculated and then tabulated to see the dynamics of the population. Observation results indicate that there are two types of fruit flies that attack plants with a very high number of fruit fly population of 67,955. This population is very dynamic and fluctuating where the number begins to decline sharply at the end of the third week from 6,609 to 128.